Comparative characteristic of alternative density models along the DSS profile N 17 - Kozlenko, M.V.; Kozlenko, Yu.V. (Geofizicheskiy Zhurnal, 2017)
Analysis of density model plotted on the base of tomographic calculations has shown that the hypothesis of the obduction nature of jointing of the Crimea and the Black Sea is groundless. Earth's crust deep structure obtained can be much more logically explained by basification of the basement as a result of being intruded by mantle irruptions of sheeted type with different compositions. Comparison of alternative density models along DSS profile N17 has shown that despite all the differences in the sections some part of the aquatic area from the East Crimea to East Black Sea depression is under-laid by the crust of sub-continental type, at the base of the Sorokin flexure there is compacted magmatogenic body, under the Tetyayev terrace the pronounced "roots" are absent that is not specific to positive geo-structural forms. The identical accuracy of selection of gravity force in both cases as well as correlation of deep structure with distribution of earthquakes does not allow finding out unambiguously which of the models is more correct. Analysis of fault tectonics and isostatic balance makes possible to give some more acceptability to rift origin of continental margin of the East Crimea